The Role of PIK-Adolescent Peer Counselors in the Efficient Use of Smartphones among Students at SMA Negeri 11 Medan - M David Kurniawan; Sri Ngayoumi Yudha Wastuti (Edumaspul: Jurnal Pendidikan, 2024)
The development of communication and information technology is increasing rapidly in the current digital era. One of them is a smartphone which is owned by almost all levels of society. This research aims to analyze the role of PIK-Remaja peer counselors in increasing the efficiency of smartphone use among students at SMA Negeri 11 Medan. This research uses a qualitative approach with a case study method. Data collection was carried out through observation and in-depth interviews with PIK-Temaja counselor teachers and students who used smartphones. The research results show that PIK-Remaja peer counselors play a role in increasing the efficiency of smartphone use through services and counseling for students. Peer counselors encourage students to use smartphones wisely which has a positive impact, such as as a communication tool, increasing knowledge and expanding relationships. On the other hand, peer counselors also warn of the dangers of excessive use of smartphones which can disrupt students' growth and development and learning. This research recommends increasing the role of peer counselors in guiding students to use smartphones efficiently and productively.